2018
DOI: 10.2478/raon-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve ultrasound for fluid status assessment in patients with severe preeclampsia

Abstract: BackgroundThere are no data on usefulness of optic nerve sheath diameter (ONSD) as a marker of patient’s fluid status in preeclampsia. The objective was to examine potential correlation between ONSD and lung ultrasound estimates of extravascular lung water in severe preeclampsia.Patients and methodsThirty patients with severe preeclampsia were included. Optic and lung ultrasound were performed within 24 hours from delivery. ONSD was measured 3 mm behind the globe. Lung ultrasound Echo Comet Score (ECS) was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 32 publications
(45 reference statements)
1
21
0
1
Order By: Relevance
“…Supporting our results that ONSD could indicate the volume status, the results of Chen et al, study which demonstrated that in patients after cardiac surgery changes of ONSD were related to changes of central venous pressure and inferior vena cava diameter as well as the cumulative fluid balance and they reported that ONSD measurement could help in cerebral edema assessment and its changes dynamically mirror volume status changes in patients post-cardiac surgery [15]. Also, our findings are in accordance with Brzan Simenc et al, who evaluated the use of ONSD measured within 24 hours from delivery in fluid assessment of thirty severe preeclampsia patients by investigating its relation with EVLW estimated by lung ultrasound and found that the median ONSD was 5.7 mm and median ECS value 19 with significant correlation between them and they concluded that optic nerve ultrasound is a helpful diagnostic tool for detection of preeclampsia patients with fluid overload [21].…”
Section: Discussionsupporting
confidence: 90%
“…Supporting our results that ONSD could indicate the volume status, the results of Chen et al, study which demonstrated that in patients after cardiac surgery changes of ONSD were related to changes of central venous pressure and inferior vena cava diameter as well as the cumulative fluid balance and they reported that ONSD measurement could help in cerebral edema assessment and its changes dynamically mirror volume status changes in patients post-cardiac surgery [15]. Also, our findings are in accordance with Brzan Simenc et al, who evaluated the use of ONSD measured within 24 hours from delivery in fluid assessment of thirty severe preeclampsia patients by investigating its relation with EVLW estimated by lung ultrasound and found that the median ONSD was 5.7 mm and median ECS value 19 with significant correlation between them and they concluded that optic nerve ultrasound is a helpful diagnostic tool for detection of preeclampsia patients with fluid overload [21].…”
Section: Discussionsupporting
confidence: 90%
“…Anatomical continuity refers to unrestricted flow of cerebrospinal fluid between the subarachnoid area around the optic nerve and intracranially. Increased ONSD is caused by an increase in pressure inside the intracranial compartment, which causes swelling of the optic nerve (papilledema) [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Increased ONSD, on the other hand, isn't clear if it may be utilized as a measure of systemic tissue edema and fluid overload. Optic ultrasonography may be utilized to evaluate fluid status and guide peripartum fluid treatment in patients with severe preeclampsia, according to Simenc [6].…”
Section: Introductionmentioning
confidence: 99%
“…Der „optical nerve sheath diameter“ (ONSD) kann möglicherweise sowohl zur Diagnose von Hirndruck als auch zur Abschätzung des Volumenstatus bei Patientinnen mit Präeklampsie genutzt werden. Aufgrund unklarer Grenzwerte sind Vorhersage und Screening der Präeklampsie auf diese Weise bisher allerdings nicht etabliert [ 27 , 28 , 29 ]. Eine Kombination mit der nichtinvasiven Messung der zerebralen Sauerstoffsättigung ( Nah-Infrarot-Spektroskopie
Nah-Infrarot-Spektroskopie
, NIRS) scheint die Aussagekraft der Methode zu verbessern [ 30 ].…”
Section: Präeklampsie Eklampsie Und Hellp-syndromunclassified